French-German cooperation in the European union in 2007-2013 - Koszel, Bogdan (My University, 2018)
The author discusses the thesis that in the arduous circumstances of the 21st century France passed the test of cooperation with the united Germany. The French-German “integration engine” scored both successes and failures, but did not break down. Germany governed by Chancellor Merkel proved to be a loyal and predictable partner, while France during Sarkozy’s presidency did not venture any steps that would strain this cooperation. A real test of the German-French leadership of the EU came with the financial crisis of the Eurozone. President Sarkozy understood the situation better and reacted faster to the growing threats, whereas Germany, for internal reasons, delayed launching large-scale rescue actions. Nevertheless, the signing of the fiscal union pact was the effect of a compromise between the two partners and yet another proof of the stability of the German-French cooperation.

Autor w artykule przedstawia tezę, że początki XXI w, stanowiły duże wyzwanie dla współpracy Niemiec i Francji w Unii Europejskiej. Francusko-niemiecki „motor integracji” zacinał się, ale nie doszło do jego załamania. Rząd niemiecki kierowany przez kanclerz Merkel lojalnie i odpowiedzialnie współpracował z Francją w okresie prezydentury Sarkozy’ego. Prawdziwy test dla przywództwa Niemiec i Francji w Unii Europejskiej nastąpił w okresie kryzysu finansowego strefy euro. Prezydent Sarkozy lepiej rozpoznał sytuację i szybciej reagował na powstające zagrożenia. Niemcy ze względów wewnętrznych spowalniały akcję ratunkową. Jednakże podpisanie paktu fiskalnego było efektem kompromisu pomiędzy obu partnerami i kolejnym udanym sprawdzianem dla stabilności współpracy niemiecko-francuskiej.
Francusko-niemiecka współpraca w Unii Europejskiej (2007-2013)
Keywords: France-Germany- European Union-cooperation; XXI w.; współpraca Niemiec i Francji; Unia Europejska; European Union